Memória das águas da cidade de Manaus – um patrimônio material e imaterial - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
The absence of procedures and routines for the conservation of the historical heritage of the city of Manaus, located in the Brazilian Western Amazon, with regard to basic sanitation, it has been characterized as one of the main responsible for erasing the memory of a historical epoch. Research and map the history of sanitation buildings in the city of Manaus, and their contribution in the sociocultural context, will make available and guarantee for future generations the preservation of part of the history of Manaus. It is understood that this can be achieved through a proposal to restore the goods threatened by mischaracterization, seeking to follow the initial conception, aiming at its reuse by society, proposing the tipping, to prevent the abandonment and destruction of property, saving its affective value. This thesis analyzed and researched the technical, political and sociocutural aspects relevant to the preservation of the memory of basic sanitation of the City of Manaus in the period from the context of rubber to contemporaneity. This thesis deals with some basic sanitation works related to the metioned period, considering the survey of the technical and historical details of the properties recognized as of greater relevance for the proposed period entitled as Complexo da Castelhana, formed by The Water Distribution Reservoir of Castelhana Baixa (Castelinho) and Castelhana Alta (reinforced concrete reservoir), Complexo do Mocó, formed by The Mocó Velho Reservoir (metallic reservoir) and the Mocó Novo (reinforced concrete reservoir), Sewer Chimney and Drainage Gallery of the Ingleses, following norms, legislation and some management techniques. It is noteworthy that protecting, preserving and recovering the memory of the historic heritage of basic sanitation in the city of Manaus implies discussing historical, architectural, affective memory, and even political power, discussing and highlighting public policies with essential practices in a multidisciplinary context of space and time. The methodological procedure is characterized as qualitative, where the theoretical-methodological model adopted for this thesis is directed to a descriptive research, opting for the following procedures: bibliographic, documentary and field, in addition to the photographic record. This research presents the collected data and allows us to confirm that the restoration for reuse of sanitation works, carried out within norms, legislation, procedures and criteria, and in partnership with municipal, state and federal agencies, constitutes into a significant and important tool for preserving the memory of the historical heritage of the city of Manaus, capital of Amazonas.
Keywords: Saúde pública - Manaus (AM); Saneamento - Manaus (AM); CIENCIAS HUMANAS; Saneamento básico; Preservação; Memória; Patrimônio histórico